2022
DOI: 10.1111/omi.12403
|View full text |Cite
|
Sign up to set email alerts
|

Role of oral microbiome in oral oncogenesis, tumor progression, and metastasis

Abstract: Squamous cell carcinoma is the most common malignant tumor of the oral cavity and its adjacent sites, which endangers the physical and mental health of patients and has a complex etiology. Chronic infection is considered to be a risk factor in cancer development. Evidence suggests that periodontal pathogens, such as Porphyromonas gingivalis, Fusobacterium nucleatum, and Treponema denticola, are associated with oral squamous cell carcinoma (OSCC). They can stimulate tumorigenesis by promoting epithelial cells p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 185 publications
0
17
0
1
Order By: Relevance
“…81 Similarly, the oral cavity also harbours a vast collection of bacteria, viruses, and fungi and any irregularity in the normal oral microbiome has been associated with aggravating oral cancer progression. 82 A few bacterial competitions are identified in HPV-related tumours as well, where the microbial interactions among themselves are not always detrimental to the host and certain specific interactions may also help in the clearance of the infection. Candida vaginitis, a fungal species residing as part of the normal flora in the cervicovaginal region, is a perfect example for this kind of interaction.…”
Section: Beneficial Co-existing Microbes For Human Papillomavirus Cle...mentioning
confidence: 99%
See 1 more Smart Citation
“…81 Similarly, the oral cavity also harbours a vast collection of bacteria, viruses, and fungi and any irregularity in the normal oral microbiome has been associated with aggravating oral cancer progression. 82 A few bacterial competitions are identified in HPV-related tumours as well, where the microbial interactions among themselves are not always detrimental to the host and certain specific interactions may also help in the clearance of the infection. Candida vaginitis, a fungal species residing as part of the normal flora in the cervicovaginal region, is a perfect example for this kind of interaction.…”
Section: Beneficial Co-existing Microbes For Human Papillomavirus Cle...mentioning
confidence: 99%
“…A dysregulated expression of the aforementioned facets can indicate BV in cervicovaginal region 81 . Similarly, the oral cavity also harbours a vast collection of bacteria, viruses, and fungi and any irregularity in the normal oral microbiome has been associated with aggravating oral cancer progression 82 …”
Section: Beneficial Co‐existing Microbes For Human Papillomavirus Cle...mentioning
confidence: 99%
“…Consequently, there is increasing awareness of the crucial role of periodontopathogenic bacteria in oral squamous cell carcinoma. Li et al reported that P. gingivalis , F. nucleatum , and T. denticola could stimulate oral squamous cell carcinoma (OSCC) by promoting epithelial cell proliferation, inhibiting apoptosis, and modulating the inflammatory microenvironment [ 124 ]. Microbial dysbiosis may serve as a bridge between periodontal diseases and oral cancer [ 125 ], and the next question is whether viruses are involved in the progression.…”
Section: Phage Vaccines: An Option For Oral Cancer Controlmentioning
confidence: 99%
“…Therefore, a standardized technique is needed in the future to regulate sampling procedures. Chronic infection is considered a risk factor in the development of cancer [ 81 ]. Evidence suggests that periodontal pathogens, such as Porphyromonas gingivalis , Fusobacterium nucleatum , and Treponema denticola , are associated with OSCC [ 81 ].…”
Section: The Role Of Oral and Vaginal Microbiota In Viral Oncogenesismentioning
confidence: 99%
“…Chronic infection is considered a risk factor in the development of cancer [ 81 ]. Evidence suggests that periodontal pathogens, such as Porphyromonas gingivalis , Fusobacterium nucleatum , and Treponema denticola , are associated with OSCC [ 81 ]. They can stimulate tumorigenesis by promoting epithelial cell proliferation while inhibiting apoptosis and regulating the inflammatory microenvironment.…”
Section: The Role Of Oral and Vaginal Microbiota In Viral Oncogenesismentioning
confidence: 99%